Development of fragility curves for road embankments exposed to perpendicular debris flows. Issue 1 (1st January 2021) - Nieto, Natalia; Chamorro, Alondra; Echaveguren, Tomás; Sáez, Esteban; González, Alvaro
Abstract: Debris flows cause recurrent interruptions and permanent damages in rural road networks, representing significant economic losses. Embankments are road assets frequently exposed to debris flows, especially in mountainous areas. The potential risk of infrastructure exposed to debris flows can be assessed in terms of the probability of expected damage based on fragility curves. The aim of the study is to develop fragility curves for road embankments exposed to debris flows representative to the expected physical damage and capacity loss. Two conceptual models are proposed to describe the impact and erosion of debris flows that run perpendicularly to road embankments. Probabilistic models are then developed in terms of limit state functions and the simulation of potential scenarios. The resulting models are finally fit to log-normal distributions and compared to historical data. Headcut erosion has higher probabilities of occurrence compared to sliding failure caused by the impact of debris flow. Lower road embankments present higher probabilities of failure to the impact of debris flows, especially for dense flows. Whereas, longer interaction times of less dense flows increase the probability of headcut erosion. Two-lane roads may present 50% more probabilities of headcut erosion compared to multilane roads for similar debris flows intensity.